Mechanics of materials - De Silva, Clarence W. (Computational mechanics and applied analysis, 2014)
Mechanics of Materials uniformly incorporates the fundamentals into analytical methods, modeling approaches, numerical methods, experimental procedures, and design techniques in a systematic manner throughout the main chapters. The practical application of the concepts, approaches, and tools presented in the introductory chapters is demonstrated through a comprehensive set of examples and case studies. Designed as an engineering textbook, the book is an outgrowth of the author's experience in teaching an undergraduate course in mechanics of materials for a large class consisting of mechanical, manufacturing, materials, and mineral engineering students, and in teaching other courses in statics, dynamics, modeling, vibration, instrumentation, testing, and design. In view of the practical considerations, design issues, and engineering techniques presented throughout the book, as well as the simplified and snapshot-style presentation of more advanced theory and concepts, the book also serves as a useful reference tool for engineers, technicians, project managers, and other practicing professionals